2022
DOI: 10.3988/jcn.2022.18.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Thickness and Echo Intensity in Chronic Stroke Survivors: A 2-Year Longitudinal Study

Abstract: Background and Purpose The objective of this study was to identify 2-year longitudinal changes in the muscle thickness (MT) and echo intensity (EI) of the abdominal, thigh, and lower limb muscles in chronic stroke survivors. Methods This study included 15 chronic stroke survivors aged 74.1±9.9 years. The MT, EI, and subcutaneous fat thickness values of the following muscles on the paretic and nonparetic sides were assessed on transverse ultrasound images: rectus abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Previous research has reported that muscle EI is negatively correlated with MT in older adults [ 26 ]. Another study reported that changes in muscle EI were significantly associated with changes in BMI [ 27 ]. These findings imply that muscle EI has a more complicated relationship with MT and other demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that muscle EI is negatively correlated with MT in older adults [ 26 ]. Another study reported that changes in muscle EI were significantly associated with changes in BMI [ 27 ]. These findings imply that muscle EI has a more complicated relationship with MT and other demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the current assessment indicators being able to reflect behavioral alterations, they do not precisely reflect skeletal muscle changes after stroke. According to published clinical and basic studies, skeletal muscle injury after stroke primarily occurs in the transverse muscle [ 47 ]. Therefore, we refer to the studies from transverse muscle atrophy [ 48 ], including the treadmill and pull tests [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, several longitudinal studies revealed that the changes in EI predict functional recovery or affect physical activity and clinical outcomes in community-dwelling older adults or patients with neuromuscular diseases. 28,[53][54][55] In consideration of the above-mentioned findings, muscle US was able to assess the quantitative and qualitative changes in skeletal muscle efficiently and better and could be an alternative to ASMI.…”
Section: Discussionmentioning
confidence: 99%